ROLE OF LECTURERS AS A JOURNALISM EDUCATOR - Diyah Yuli Sugiarti (Jurnal Metamorfosa, 2019)
The purpose of this research is to determine the role of lecturers as journalism educator. This research uses quantitative approach. Data was taken from the literature analysis, observations and interviews to lecturers at Islamic University "45" in Bekasi city. The results showed that there were very low lecturers as journalism educator, namely 5% from 137 lecturers. This will be weakness because: 1) low awareness about writing to the mass media, They don’t have much timedue to teaching activities, They don’t have the journalistic knowledge, limited writing skills in mass media, lecturers' reading and writing for the mass media is very low, and the culture of the organization is not supportive. This condition causes the education quality assurance system notoptimal. If left unchecked it will hamper Indonesia's national education goals. So it needsefforts to increase the awareness of the role of lecturers as journalis educator.